Pengaruh Model Pembelajaran Kooperatif Tipe STAD Berbantuan GeoGebra pada Materi Bangun Ruang terhadap Minat dan Hasil Belajar Siswa Kelas V SD - Kuyani Desi Safitri; Ahmad Muzaki; Sanapiah Sanapiah; Zainal Abidin (Jurnal Kependidikan Ki Hajar Dewantara, 2026)
The low levels of students’ interest and learning outcomes in solid geometry indicate the need for instructional models and media that can increase student engagement and facilitate the visualization of geometric concepts. This study aimed to analyze the effect of the GeoGebra-assisted Student Teams Achievement Division (STAD) cooperative learning model on fifth-grade elementary students’ learning interest and achievement. A quantitative approach with a quasi-experimental pretest–posttest control group design was employed. The sample consisted of 33 students, including 18 students in the experimental group at SD Negeri 1 Marong and 15 students in the control group at SD Negeri 2 Marong. The experimental group received GeoGebra-assisted STAD instruction, whereas the control group received STAD instruction without GeoGebra. Data were collected through an achievement test, a learning-interest questionnaire, and documentation. The data were analyzed using the Shapiro–Wilk test, Levene’s test, an independent-samples t-test, and normalized gain analysis. The results showed that the experimental group’s mean achievement score increased from 30.27 to 60.83, whereas the control group’s score increased from 24.33 to 44.00. The hypothesis test yielded (t=2.948) with a significance value of 0.006, indicating a significant difference in learning outcomes between the two groups. The experimental group obtained a mean N-Gain of 44.38%, categorized as moderate, whereas the control group obtained 25.94%, categorized as low. The learning-interest score increased by 13.00 points in the experimental group and by 8.87 points in the control group. Therefore, GeoGebra-assisted STAD positively affected students’ learning outcomes and showed a greater descriptive increase in learning interest than STAD without GeoGebra